Effects of zeolite application on grain yield, water use and nitrogen uptake of rice under alternate wetting and drying irrigation - Zheng, Junlin; Chen, Taotao; Xia, Guimin; Chen, Wei; Liu, Guangyan; Chi, Daocai (International Journal of Agricultural and Biological Engineering, 2018)
With the increasing scarcity of water resources and growing population, the dual goal of saving irrigation water and increasing grain yield has become a major challenge in rice production around the world. A two-year lysimetric experiment was conducted to assess the effects of zeolite application (Z0: 0 and Z1: 15 t/hm2) and water regimes (W0: continuous flooding irrigation, W1: energy-controlled irrigation, W2: alternate wetting and drying irrigation) on grain yield, water use and total nitrogen uptake of rice. Zeolite addition to paddy field significantly increased grain yield, total N uptake, and water use efficiency (WUE), despite a negligible effect on amount of irrigation water used. Compared with W0, the separate use of W1 and W2 each considerably decreased irrigation water. However, W2-grown rice showed a significant decline in grain yield. In contrast, W1 showed comparable grain yield with W0, and achieved the highest WUE. Correlation analysis revealed that grain yield was significantly and positively correlated with effective panicles, spikelets per panicle, water consumption, and total N uptake. It is concluded that the combination of zeolite application at the rate of 15 t/hm2 and energy-controlled irrigation could be recommended to benefit farmers by reducing irrigation water while improving grain yield on a clay loam soil.Keywords: zeolite, alternate wetting and drying irrigation, rice, yield, water use efficiencyDOI: 10.25165/j.ijabe.20181101.3064Citation: Zheng J L, Chen T T, Xia G M, Chen W, Liu G Y, Chi D C. Effects of zeolite application on grain yield, water use and nitrogen uptake of rice under alternate wetting and drying irrigation. Int J Agric & Biol Eng, 2018; 11(1): 157–164.